Kombinasi Numerasi dan Permainan Tradisional yang Menyenangkan dalam Satu Latar (Lapangan Bangun Datar) di SD Negeri 33 Cakranegara - Khairunnisa, Izzati; Hati, Intan Permata; Jannah, Fitriatul; Hendriawan, M. Zulia; Lu'luilmaknun, Ulfa (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
Numeracy skills are very important for students to possess. Numeracy skills can help understand and interpret quantitative information encountered in everyday life. However, there are still students at SD Negeri 33 Cakranegara who have low numeracy skills. This is due to the lack of initial understanding of numeracy and students' interest in learning. The purpose of this activity is to foster students' interest in learning and understanding of numeracy. LATAR (Lapangan Bangun Datar) is one of the work programs of Kampus Mengajar Batch 8 at SD Negeri 33 Cakranegara which is expected to be a solution to this problem. It is called LATAR because it uses a field as the main container for making shapes in the form of circles, parallelograms, trapezoids, rhombuses and a picture of a traditional dengklaq game. The implementation method of the LATAR program includes preparation, implementation, and reporting. This activity involved 20 grade V students. The data were collected through a validated response questionnaire. The results of this activity received a positive response from students. It is concluded that the use of LATAR media can foster students' interest in learning and understanding of the concept of shapes.